Rejection of Transplanted Organ in the Legal System of Civil Liability in Iran: civil liability arising from rejection of transplanted organ - Rostami Chelkasari , Ebadolah; Khafi , Saeid (Bioethics and Health Law Journal (BHL), 2021)
Background and Aim: Rejection of transplanted organs refers to a phenomenon where the immune system of the recipient body refuses to accept the transplanted organ. This review is conducted to identify the liability of the health staff in complications of the organ transplantation process and in particular, the role of donor and recipient in the liability arising from it. Materials and Methods: In the present review, utilizing the keywords of organ transplantation, civil liability, and rejection in databases of Magiran, Google, SID, the related articles are studied and analyzed. Ethical Considerations: Honesty in the literature and citation analysis and reporting were considered. Findings: The liability arising from rejection and other complications of transplantation, has usually a contractual figure, and unlike other medical responsibilities, it has a feature that there are two contracts of "transfer of organ between donor and recipient" and "therapy contract" behind it. In cases where transplant rejection is caused by a defect in the transplanted organ and the donor is aware of it, transplant rejection is attributed to the recipient with no goodwill; with violation of "implied term of the transplanted organ health" in the contract between the donor and recipient, his liability is the case. The therapy contract follows the general rule enacted by the new Islamic Penal Code adopted in 2013, and the doctor and other factors that caused transplant rejection, in case of fault, are responsible for compensation for the damages to the transplanted organ recipient. Conclusion: In principle, donor and devisees of a person who is brain dead, in many cases, are exempt from the liability arising from transplant rejection or other complications, according to the benefaction rule, and in cases where transplant rejection is attributed to the recipient, he/she is exempt from compensation. *Corresponding Author: Ebadolah Rostami Chelkasari; Email: e-rostamy@guilan.ac.ir; ORCID: https://orcid.org/0000-0002-3969-3284 Please cite this article as: Rostami Chelkasari E, Khafi S. Rejection of Transplanted Organ in the Legal System of Civil Liability in Iran. Bioeth Health Law J. 2021; 1:1-9: (e12). http://doi.org/10.22037/bhl.v1i1.38156